Mergers and Alliances in Higher Education: International Practice and Emerging Opportunities - Curaj, A (Springer, 2016)
This volume casts light on mergers and alliances in higher education by examining developments of this type in different countries. It combines the direct experiences of those at the heart of such transformations, university leaders and senior officials responsible for higher education policy, with expert analysts of the systems concerned.